RESPON PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) PADA MEDIA GAMBUT TERHADAP PEMBERIAN ABU JANJANG KOSONG KELAPA SAWIT DAN PUPUK N - Mutia Fadhila; Wawan Wawan; Isna Rahma Dini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to determine the interaction of oil palm bunch ashand N fertilizer and to get the best dose to the cocoa seedlings growth on peat media. This research was conducted from Desember 2016 to March 2017. This research is a 4 x 4 factorial experiment arranged in a completely randomized design (CRD) with three replications. The first factor is oil palm bunch ash with four levels namely 0, 2,5, 5 and 7,5 tons/ha. The second factor was the N fertilizer with four levels namely 0, 0,12, 0,16 and 0,20 tons/ha. Parameters observed were plant height, number of leaves,girth trunk, root volume, shoot roots ratio and the dry weight. The results showed that the interaction of oil palm bunch ash and N fertilizeronnumber of leaves,girth trunk, root volume, and the dry weight was significantlyaffect, the best treatment can be obtained by providing a dose of oil palm bunch ash7,5 tons/ha and N fertilizer0,20 tons/ha. Oil palm bunch ashgives the best treatment results with dose of 7,5 tons/ha significantly affect on plant height, number of leaves, girth trunk, root volume, shootroots ratioand dry weight. Provision of N fertilizer to the cocoa seedlings significantly affect on plant height, number of leaves, girth trunk, root volume, shootroots ratioand dry weight and providing ofN fertilizer0,20 tons/ha is best dose.Keywords:Oil palm bunch ash, Fertilizer N, Cocoa seedlings